DA'I COMPETENCE IN THE DIGITAL ERA (CASE STUDY OF NING UMMI LAILA'S DA'WAH DELIVERY) - Hanifah, Najmy; Ramadhan, Zukhrufi Izza; Diansah, Edo Ardo Arta; Prasongko, Wahyu Agung; Aziz, Moh. Ali; Mualimin (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2024)
One of the biggest changes is the surge in the number of new da'i appearing on various online platforms. This phenomenon can be considered a positive outcome of the increasing global connectivity in the digital era. This research uses descriptive qualitative research with a case study approach to da'iyah Ning Ummi Lailatul Rahma Hadi as a young preacher who is in the media spotlight based on the perspective of 'Abd Karim Zaidan. The results of the study are Ning Ummi Laila has religious knowledge competence, faith and spirituality in Allah SWT, has good morals and the ability to use social media in da'wah.